1989
DOI: 10.1212/wnl.39.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of pyruvate dehydrogenase complex (PDHC) in Leigh's disease fibroblasts

Abstract: Several groups have reported abnormalities of the pyruvate dehydrogenase complex (PDHC) in cultured cells or other tissues from patients with Leigh's disease (subacute necrotizing encephalomyelopathy). We therefore undertook studies to elucidate the molecular basis of the defect of PDHC in cultured skin fibroblasts from two patients with Leigh's disease. The deficit of total PDHC activity in homogenates of Leigh's disease fibroblasts could be restored by adding exogenous lipoamide dehydrogenase (LAD, E3), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The similar values of DLD enzymatic activity among all three genotypic classes provides a likely explanation for why there are no phenotypic differences between these three groups. The DLD activity in −/− blastocysts is almost certainly from maternal DLD protein since this mutation completely ablates enzymatic activity and there are numerous gene (Feigenbaum and Robinson, 1993; Johnson et al ., 1997a) and protein (Williams, 1991; Hinman et al , 1989) studies in a variety of mammalian species indicating that no other protein can replace the function of DLD. Previous studies of Dld heterozygous mice and clinical data also strongly support that 44% residual activity is sufficient for normal cellular function and it has been shown that embryonic stem cells with 50% DLD activity can be maintained in culture and can contribute to all tissues of the mouse following blastocyst injection (Johnson et al , 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…The similar values of DLD enzymatic activity among all three genotypic classes provides a likely explanation for why there are no phenotypic differences between these three groups. The DLD activity in −/− blastocysts is almost certainly from maternal DLD protein since this mutation completely ablates enzymatic activity and there are numerous gene (Feigenbaum and Robinson, 1993; Johnson et al ., 1997a) and protein (Williams, 1991; Hinman et al , 1989) studies in a variety of mammalian species indicating that no other protein can replace the function of DLD. Previous studies of Dld heterozygous mice and clinical data also strongly support that 44% residual activity is sufficient for normal cellular function and it has been shown that embryonic stem cells with 50% DLD activity can be maintained in culture and can contribute to all tissues of the mouse following blastocyst injection (Johnson et al , 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in pyruvate dehydrogenase have also been found to be generalized but to differ from organ to organ. 18,20,24,25 Organs affected may be those with decreased levels of enzyme or an altered enzyme. The age of onset may depend on the severity of enzyme deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in carbohydrate metabolism due to a dysfunction of the PDC complex are well established for a number of neurodegenerative disorders, such as cerebellar and spinal ataxias (Reynolds and Blass, 1976;Blass and Gibson, 1978;Kark and Rodriguez-Budelli, 1979), and several neurological inborn diseases (Blass, 1983) including Leigh's disease (DeVivo et al, 1979;Evans, 1981;Hinman et al, 1989) as well as for Huntington's disease (Sorbi et al, 1983) and Alzheimer's disease (Perry et al, 1980;Sorbi et al, 1983;Sheu et al, 1985). The mechanism ofbrain damage under these conditions is poorly understood, and an impaired production of energy in the form of ATP or energy charge potential might be the most likely explanation (Atkinson, 1968).…”
Section: Discussionmentioning
confidence: 99%